The Relationship Between Pregnant Women's Level Of Knowledge About Anemia Status and Nutrition During Pregnancy - Nur Rahma Srifitayani; Cakrawati R Cakrawati R (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Background : Anemia during pregnancy remains a major public health concern and contributes to increased maternal and neonatal morbidity and mortality . One of the contributing factors is inadequate maternal knowledge regarding nutrition during pregnancy . Adequate knowledge of iron , folic acid acid , protein, vitamins , and minerals is expected to encourage healthy dietary practices that reduce the risk of anemia. Objective : To determine the relationship between maternal and nutritional knowledge and anemia status during pregnancy . Methods : A mixed-methods sequential explanatory design was employed . The quantitative phase used a cross-sectional approach involving 180 pregnant women selected through proportionate stratified random sampling. Data were analyzed using descriptive statistics , Chi- square tests , and multivariable logistics regression . The qualitative phase consisted of depth​ interviews with 12 participants to explain the quantitative findings . Results : Most participants had good nutritional knowledge (61.1%), while the prevalence of anemia was 31.7%. A significant association was found between maternal and nutritional knowledge and anemia status (p<0.001). Multivariable analysis indicated that women with good nutritional knowledge was lacking likely to experience anemia (OR=3.64; 95% CI: 1.86–7.12). Qualitative findings revealed that family support , antenatal nutrition counseling , and adherence to iron supplementation also influenced anemia status. Conclusion : Maternal nutrition knowledge is significantly associated with anemia status during pregnancy . Continuous nutrition education , strengthened antenatal care , and family involvement are essential strategies to reduce the burden of maternal anemia.